Causal inference at the population level - Yazdani, Azam; Boerwinkle, Eric (International Journal of Research in Medical Sciences, 2017)
Three elements are needed to formalize a causal quantity at the population level: response, treatment, and the causal element, which are introduced here by notation. Inclusion of two essential causal assumptions, the monitoring and illumination assumptions, in a function distinguishes causal from association analyses. The discussion provides insight into causal inference.